PEMBELAJARAN BIMBINGAN KARIER DENGAN MENGGUNAKAN MEDIA POWERPOINT BERBASIS GAMBAR UNTUK MENINGKATKAN KINERJA AKADEMIK MAHASISWA - Hartono, Hartono Hartono (Jurnal Bimbingan dan Konseling Terapan, 2020)
Career guidance instructional is an intracuricular activity that must be taken by every student of a guidance and counseling study program. This course is one of the subjects to form student mastery competencies on the basic concepts, theories and application of guidance and counseling services. This study aims to examine the significance of career guidance instructional using image-based PowerPoint media to improve students academic performance, which is carried out using a quasi-experimental method. The population of this research is 300 students of guidance and counseling study program at University of PGRI Adi Buana Surabaya. The research sample was taken using class lottery techniques, obtained 33 students as the experimental group and 23 students as the control group. Students academic performance data were collected by using multiple choice test forms developed by researchers through content validity procedures, which were analyzed using the SPSS t test of parametric statistic techniques of program for Windows version 23.0. The results of data analysis obtained t value of .312 at a significant level of .756 which means not significant. The conclusion of this research is that career guidance instructional using image-based PowerPoint media significantly cannot improve students academic performance. In connection with the findings of this study, it is recommended that more similar research be carried out by increasing the use of more comprehensive image-based PowerPoint media